Interleukin-1 blockade in acute decompensated heart failure: A randomized, double-blinded, placebo-controlled pilot study - Van Tassell, Benjamin W. (J Cardiovasc Pharmacol, 2016)
BACKGROUND: Heart failure is an inflammatory disease. Patients with acute decompensated heart failure (ADHF) exhibit significant inflammatory activity upon admission. We hypothesized that Interleukin-1 (IL-1) blockade, with anakinra (Kineret™, Swedish Orphan Biovitrum), would quench the acute inflammatory response in patients with ADHF. METHODS: We randomized 30 patients with ADHF, reduced left ventricular ejection fraction (LVEF<40%), and elevated C reactive protein (CRP) levels (≥5 mg/L) to either anakinra 100 mg twice daily for 3 days followed by once daily for 11 days or matching placebo, in a 1:1 double blinded fashion. We measured daily CRP plasma levels using a high-sensitivity assay during hospitalization and then again at 14 days and evaluated the area-under-the-curve (AUC) and interval changes (delta). RESULTS: Treatment with anakinra was well tolerated. At 72 hours, anakinra reduced CRP by 61% versus baseline, compared to a 6% reduction among patients receiving placebo (P=0.004 anakinra versus placebo). CONCLUSIONS: IL-1 blockade with anakinra reduces the systemic inflammatory response in patients with ADHF. Further studies are warranted to determine whether this anti-inflammatory effect translates into improved clinical outcomes.